1846PBiomarker testing of lung cancer in Spain. (1st October 2019) - Rodriguez Abreu, D; Guirado, M; Camps Herrero, C J; Bosch Barrera, J; Bernabé, R; Casal, J; García-Campelo, M-R; Gonzalez-Larriba, J L; Massuti Sureda, B; Ortega Granados, A L; Domine Gomez, M; Sala, M A; et al.
Abstract: Background: Target therapy guide by biomarkers have become the standard of care for patients with lung cancer (LC). So, identify those molecular alterations is one of the most important care needs nowdays. Our objective was to know the implementation degree of these tests in a large cohort of patients in Spain using the Thoracic Tumor Registry (TTR) of the Grupo Español de Cáncer de Pulmón (Spanish Lung Cancer Group). Methods: The TTR is an observational cohort multicenter study of LC in Spain. The study is conducted according to the Declaration of Helsinki and approved by the institutional review board of each participating institute. The registry was approved by the Spanish Drug Agency as a non-post-authorization, non-interventional study. We analyzed the molecular biomarkers considering all stages of LC. Results: A total of 7, 872 patients from 58 Spanish centers were enrolled between August 2016 to December 2018. The most frequent screened molecular test was the EGFR mutations, it was performed in 4, 456 patients (67.5%). The proportion of biomarker evaluation has varied over time, ranging from 57.9% prior to 2012 up to 73.7% in 2017. The molecular assessment of some biomarkers reached 81.4% of these patients, with some differences between Regional Communities, regarding the molecular tests performed. Three thousand four hundred forty-six (3, 446) patients (52.2%) had a stage IV at diagnosis. There was performed some biomarker test in 92% of the 2570 patients with stage IV and non-squamous histology. In those stage IV non-squamous patients, the EGFR and ALK test were performed in 92% and 79% respectively but 2 years ago ALK test was done only in 40% of the patients. ROS1 was studied in 20% of the cases. Conclusions: Although no national plan exists for molecular biomarker analysis in Spain, the implementation of biomarkers tests in all the hospitals that contribute to the TTR is high. The increase in the ALK analysis in the last period is relevant. As we have some regional differences, it is important to understand the causes to improve them. Clinical trial identification: NCT02941458. Legal entity responsible for the study: Spanish Lung Cancer Group. Funding: Novartis, Merck Sharp and Dohme, Lilly. Disclosure: All authors have declared no conflicts of interest.